Development of Cultural Tourism Attractions in Ngasa Traditional Ceremonies through Community Empowerment in Kampung Budaya Jalawastu, Brebes Regency, Central Java - Shavira Jatu Roro Dyarti; Siti Nurul Rofiqo Irwan; Sri Rahayu Budiani (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2025)
Development of Cultural Tourism Attractions in Ngasa Traditional Ceremonies through Community Empowerment in Kampung Budaya Jalawastu, Brebes Regency, Central Java. Upacara Adat Ngasa in Kampung Budaya Jalawastu is a cultural tourism attraction involving three community groups: the Kokolot Council, Jagabaya, and Laskar Wanoja. However, its development faces challenges in the form of low public awareness due to minimal economic impact. This study aims to determine the involvement and empowerment of the community in Upacara Adat Ngasa from psychological, political, and social aspects, as well as to analyze the development of the ceremony as a cultural tourism attraction. The methods used include interviews, observations, documentation, and questionnaires to 20 community group members. The results of the study showed an increase in self-esteem (psychological) and involvement in decision-making (political), but social empowerment was still weak due to low collaborative initiatives. In conclusion, community empowerment has been running, but social and political aspects need to be strengthened. The development of tourist attractions can be continued with optimal resource management.